Learning Style Preferences Among Undergraduate Medical Students: An Experience from Different Medical Colleges of Bangladesh (Bangladesh Journal of Medical Education, 2019)
This descriptive type of cross sectional study was conducted to determine the learning styles of undergraduate medical students. The study period was from July 2017 to June 2018. The study was carried out among the students of 2nd, 3rd and 4th phases of MBBS course of 3 government and 4 non-government medical colleges of Bangladesh. Out of 7 medical colleges, 4 were within Dhaka and 3 were from outside Dhaka. The sample size was 1004 students. Medical colleges were selected purposively and convenience sampling technique was adopted for data collection. Bangla translated version Fleming's VARK (visual, auditory, read/write and kinesthetic) questionnaire was used to identify the learning styles of students. The study revealed that out of 1004 medical students, 64.2% preferred multimodal learning styles and rest 35.8% preferred unimodal learning styles. Among unimodal learning preferences, auditory (A) and kinesthetic (K) were the most preferred sensory modalities of learning. Among multimodal learning styles preferences, the combination of auditory & kinesthetic (AK) and auditory, read/write & kinesthetic (ARK) were predominant. There were only significant differences of the mean scores of visual (V) learning style among the male and female students. Majority of students preferred multimodal learning styles. Students are able to learn effectively as long as the teacher provides a blend of visual, auditory, read/writing and kinesthetic activates. The study recommended that teachers should be aware of the medical students' learning styles and aligning teaching-learning methods with learning styles will improve their learning and academic performance.Bangladesh Journal of Medical Education Vol.10(2) 2019: 26-30